Menginang Sirih dan Tradisi yang Hampir Hilang pada Masyarakat Banjar serta Perspektifnya dalam Kesehatan Gigi untuk Wujudkan Indonesia Bebas Karies 2030 - Topan Sulaiman Asy’ari; Riska Amelia Safitri; Nur Shofa Fhadila; Nidaul Jannah; Chintana Aurel Hairin; fauzie21@ulm.ac.id (Health Information : Jurnal Penelitian, 2023)
Introduction: Dental health problems in Indonesia are still relatively high. Based on the 2018 Riskesdas results, the prevalence of caries in Indonesia reached 57.6%. In South Kalimantan Province, 46.90% of the population suffers from dental caries. One of the factors thought to be related to the prevalence of dental caries is the habit of "Menginang Sirih" which is the culture of the Banjar people. Objective: This study aims to analyze the relationship between the tradition of menginang sirih with the incidence of dental caries and analyzing aspects of menginang culture in society. Method: This research uses a mixed method which combines quantitative methods with a case control approach to determine the relationship between the menginang tradition and dental health and qualitatively by conducting in-depth interviews to find out cultural reasons in society. Results: The research subjects were 46 respondents, consisting of 36 women and 10 men. It was found that there was no relationship between menginang habit, age, duration of menginang habit, frequency in a week, chewing time, materials used and brushing teeth with the incidence of dental caries (p-value = 0.375; 0.964; 0.083; 1.000; 1.000; 0.462; 0.739; 0.462). Based on the results of the analysis of cultural aspects, it is known that the menginang tradition usually occurs at sacred events such as weddings, which symbolizes the union of two souls. Conclusion: The menginang tradition can be preserved by continuing to pay attention to personal hygiene and regular dental check-ups.